JSE 31:2 Editorial Summer 2017 - Braude, Stephen (Journal of Scientific Exploration, 2017)
One of the most valuable features of the early years of both the Proceedings and Journal of the Society for Psychical Research was the frequent publication of intriguing (and often scrupulously investigated) anecdotal reports. Indeed, the enterprising early SPR researchers produced some mammoth reports based on such material, including its 400-page “Report on the Census of Hallucinations” (Society for Psychical Research 1894) and the monumental Phantasms of the Living (Gurney, Myers, & Podmore 1886). The pioneers of psychical research were shrewd enough to realize that apparent spontaneous occurrences of ESP and PK, and phenomena suggestive of postmortem survival, could provide valuable clues as to the nature of psychic functioning, and that the collection and careful study of this material was an essential precursor to doing serious theoretical work in the area. Sadly, that lesson seems not to have entirely survived the gnawing tooth of time, as more and more would-be psi researchers, in a misguided attempt to appear conventionally scientific and curry favor with mainstream science, confined their activities and attention strictly to the laboratory, having little familiarity with or comprehension of the day-to-day apparent eruptions of phenomena that drove earlier researchers into the lab in the first place. I mention this now because this issue of the JSE features a contribution by Russell Targ to the material suggestive of postmortem survival—two incidents pointing to the survival of his daughter Elisabeth. The two incidents are considerably more intriguing than most, and they highlight what is probably the most recalcitrant issue in the debate over survival—namely, the apparent standoff between the survivalist and living-agent psi (LAP) interpretations of the evidence.